Using Five Main Criterions in Teaching Public Speaking to UBSI Students in the Faculty of Communication and Language Jakarta - Bobby Octavia Yuskar; Suhono Suhono (Bulletin of Science Education, 2023)
This research focuses on teaching public speaking using Five Main Criterions (FMC) to UBSI Students from the Faculty of Communication and Language. The subjects of this research are twenty students divided into two groups, ten boys and ten girls. Each student has to deliver public speaking in front of the class with different topics in limited time. The method used in this research is a qualitative research that pays attention to the utilization of Five Main Criterion as one of teaching techniques utilized by the researcher in teaching public speaking to UBSI students. Each criterion is interconnected to each other as unity that helps students in presenting their public speaking appropriately. The scoring was obtained according to the points from each criterion. This teaching technique was compiled by the researcher from numerous reliable resources. The researcher uses Five Main Criterions as a solution to enhance the level of confidence and also to improve the presentation skills of UBSI Students when they conduct public speaking task in class. There are a number of theories utilized by researcher in order to support this research to have solid scientific background. The theories were originated from a number of scholars who already conducted researchers in public speaking. The aim of this research is to provide a solution to fellow lecturers in providing suitable method in teaching public speaking to their students.. In addition, three previous researchers upon public speaking were added by the researcher as valuable sources to enrich the quality of this research. Keywords: Teaching Public Speaking, Five Main Criterions (FMC), Public Speaking